2020
DOI: 10.1128/cmr.00115-20
|View full text |Cite|
|
Sign up to set email alerts
|

New β-Lactam–β-Lactamase Inhibitor Combinations

Abstract: SUMMARY The limited armamentarium against drug-resistant Gram-negative bacilli has led to the development of several novel β-lactam–β-lactamase inhibitor combinations (BLBLIs). In this review, we summarize their spectrum of in vitro activities, mechanisms of resistance, and pharmacokinetic-pharmacodynamic (PK-PD) characteristics. A summary of available clinical data is provided per drug. Four approved BLBLIs are discussed in detail. All are options for treating multidrug-resistant (MDR) Enterobacterales and Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
253
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 321 publications
(300 citation statements)
references
References 297 publications
0
253
0
8
Order By: Relevance
“…Among them three inhibitors are now approved or in phase 3, avibactam (belonging to diazibyciclooctanone DBO), relebactam (DBO), and vaborbactam (boronic acid derivative) ( 182 ). Avibactam, formerly NXL-104, in combination with ceftazidime, proved its efficacy against class A, C, and some class D but not against class B β-lactamases ( 183 ). Among rare carbapenemases, avibactam demonstrated efficacy against CTX-M-33-, GES-5-, SME-2-producing isolates ( 42 , 184 ).…”
Section: β-Lactamase Inhibitors and Rare Carbapenemasesmentioning
confidence: 99%
See 4 more Smart Citations
“…Among them three inhibitors are now approved or in phase 3, avibactam (belonging to diazibyciclooctanone DBO), relebactam (DBO), and vaborbactam (boronic acid derivative) ( 182 ). Avibactam, formerly NXL-104, in combination with ceftazidime, proved its efficacy against class A, C, and some class D but not against class B β-lactamases ( 183 ). Among rare carbapenemases, avibactam demonstrated efficacy against CTX-M-33-, GES-5-, SME-2-producing isolates ( 42 , 184 ).…”
Section: β-Lactamase Inhibitors and Rare Carbapenemasesmentioning
confidence: 99%
“…However, this combination has limited activity against class B (NDM-, VIM-, or IMP-producing isolates) and class D (OXA-48-like-producing isolates) ( 191 ). Relebactam demonstrated inhibition toward KPC-, SHV-, CTX-M-,TEM-, or class C-β-lactamases but exhibited moderate inhibition against OXA-48-like ( 183 ). However, it has been observed that, despite activity against class A carbapenemases such as KPC, relebactam does not inhibit SME-4 enzyme ( 192 ).…”
Section: β-Lactamase Inhibitors and Rare Carbapenemasesmentioning
confidence: 99%
See 3 more Smart Citations